2018
DOI: 10.1590/fst.06817
|View full text |Cite
|
Sign up to set email alerts
|

Ozone in polycyclic aromatic hydrocarbon degradation

Abstract: Among energy sources from food, corn is a cereal with significant nutritional characteristics. However, during preprocessing, corn is subject to contamination by polycyclic aromatic hydrocarbons, which are considered carcinogenic, and gas ozone can be used as an alternative for decontamination. This study aims to evaluate the effect of ozonation on the quality of corn grains at different exposure times. Evaluations were performed to assess moisture content, electrical conductivity, germination, germination spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The bactericidal, antioxidant, and dehydration attribute of smoking lead to preserve the food in addition to adding a unique flavor, color, and aroma to the food (Cabral et al, 2021;Roseiro et al, 2012;Conde et al, 2005). However, concerns are raised about the consumption of smoked meat products mainly due to considerable amounts of PAH found in this type of food product (Silva et al, 2018;Babaoglu et al, 2017;Aghamohammadi et al, 2014;García-Falcón & Simal-Gándara, 2005;Wenzl et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The bactericidal, antioxidant, and dehydration attribute of smoking lead to preserve the food in addition to adding a unique flavor, color, and aroma to the food (Cabral et al, 2021;Roseiro et al, 2012;Conde et al, 2005). However, concerns are raised about the consumption of smoked meat products mainly due to considerable amounts of PAH found in this type of food product (Silva et al, 2018;Babaoglu et al, 2017;Aghamohammadi et al, 2014;García-Falcón & Simal-Gándara, 2005;Wenzl et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers seeking to investigate contamination by PAHs have also detected these compounds in food products. Farhadian et al (2010) studied PAHs in grilled meat and detected higher concentrations in charcoal-based grills, followed by dishes prepared in a gas oven; Collins et al (2006) described the main processes involved in the accumulation of organic compounds (including PAHs) by roots, leaves and fruits; Rojo Camargo et al (2011) detected PAHs in different brands of soybean oils available in the Brazilian market, totaling 42 samples with average levels of PAHs ranging from 10.4 to 112.0 μg kg -1 ; Tfouni et al (2018) found high concentrations of PAHs in 10 different types of teas; and Silva et al (2018) identified the contamination of PAHs in corn grains. The presence of PAHs detected in corn grains dried using direct-fired furnace can lead to contamination of derived products produced from this raw material, such as corn oil.…”
Section: Resultsmentioning
confidence: 99%
“…PAHs are compounds that can contaminate stored grains, as they can be formed in the furnaces during the drying process using direct burning of firewood as fuel and high combustion temperatures (Rozentāle et al, 2015;Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible to determine the time of exposure of each sample to the smoke during drying, as it is directly linked to the initial moisture content, and whether this influenced the level of contamination. According to Silva et al. (2018) , convective drying in a direct-fired furnace increases the level of PAHs contamination in soybean grains.…”
Section: Resultsmentioning
confidence: 99%